2018
DOI: 10.2478/dim-2018-0009
|View full text |Cite
|
Sign up to set email alerts
|

Document- and Keyword-based Author Co-citation Analysis

Abstract: In the field of scientometrics, the principal purpose for author co-citation analysis (ACA) is to map knowledge domains by quantifying the relationship between co-cited author pairs. However, traditional ACA has been criticized since its input is insufficiently informative by simply counting authors’ co-citation frequencies. To address this issue, this paper introduces a new method that reconstructs the raw co-citation matrices by regarding document unit counts and keywords of references, named as Document- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…We defined the exploration as exploring behavior level, while the exploitation as publishing behavior level. In author-keyword networks (Wang et al 2018), researchers who have slightly changed interest or focusing on fusion topics can change the network models. However in our proposed model, the change issue is controllable, since the keywords are treated as topics in a broader context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We defined the exploration as exploring behavior level, while the exploitation as publishing behavior level. In author-keyword networks (Wang et al 2018), researchers who have slightly changed interest or focusing on fusion topics can change the network models. However in our proposed model, the change issue is controllable, since the keywords are treated as topics in a broader context.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the need for tracking trends in academic articles, one-mode network of articles or keywords derived from two-mode network of article-keyword was constructed to understand key points of articles (Li et al 2016). The article-keyword network was also used in particular network type of author-article-keyword to quantify author relationships for citation analysis (Wang et al 2018). By incorporating keyword information, the analysis revealed more insights of knowledge domain mapping for authors.…”
Section: Bipartite Exploration On Author-based Networkmentioning
confidence: 99%
“…A bibliometric technique called co-citation reference analysis looks at how often two or more documents are cited in the same reference list of a third publication. The fundamental tenet of co-citation analysis is that two publications are probably connected if they are often referenced together [53] Just 37 of the 12044 cited references in this study met the required amount of citations, which is based on a cited reference having a minimum of 5. But once more, the results will be compared 27 after the study data has been manually vetted shown in figure 7.…”
Section: Co-citation References Analysismentioning
confidence: 93%
“…More recent studies have brought about improvements in the results of co-citation analysis using new ideas and techniques, namely, semantic similarity at different proximity levels (Sanguri et al ., 2020; Colavizza et al , 2018; Hsiao and Chen, 2017), probability of co-citation (Rodriguez-Prieto et al , 2019) and reconstructing raw co-citation matrices based on document unit counts and keywords of references (Wang et al ., 2018).…”
Section: Literature Reviewmentioning
confidence: 99%